Phytophotodermatitis due to chinese herbal medicine decoction - Ruzhi Zhang; Wenyuan Zhu (Wolters Kluwer Medknow Publications, 2011)
A 24-year-old female presented to the clinic complaining of bizarre patterns and linear streaks of hyperpigmentation on her legs and bizarre alutaceous patches on the neck and upper breast of her son for 7 days. Physical examination showed sharply demarcated hyperpigmented streaks on the extensor aspects of legs and bizarre brown maculae and patches on the right neck and upper chest of her son. Considering the history of Chinese herbal medicine decoction had been splashed onto these sites, phytophotodermatitis was definitely diagnosed.